Impact of Distance from the Forest Edge on The Wild Bee Diversity on the Northern Slope of Mount Slamet - Imam Widhiono; Eming Sudiana (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
In agricultural landscape in northern slope of Mount Slamet, diversity of wild bee species as pollinator depend on forested habitats. This study aimed to assess the effects of distance from the forest edge on the diversity of wild bees on strawberry and tomato crops. This study was conducted from July 2014 to October 2014. The experimental fields contained tomato and strawberry with a total area of 4 ha (2 ha each) and divided into five plots based on distance from the forest edge (0, 50, 100, 150, and 200 m). Wild bee was catched with kite netting in 7.00 -9.00 in ten consecutive days. Wild bee diversity differed according to distance from the forest edge, the highest value was at 0 m for strawberry plots (H’ = 2.008, E = 0.72 and Chao1= 16) and for tomato plots, the highest diversity was at 50 m from the forest edge (H’ = 2.298, E = 0.95 and Chao1= 11) and the lowest was at 200 m in both plots. Wild bee species richness and abundance decreased with distance, resulting in the minimum diversity and abundance of wild bee at 200 m from forest edge in both crops. How to CiteWidhiono, I., Sudiana, E. (2016). Impact of Distance from the Forest Edge on The Wild Bee Diversity on the Northern Slope of Mount Slamet. Biosaintifika: Journal of Biology Biology Education, 8(2), 148-154.